Calculation of Adsorption free energy of Aromatic Compounds on Graphene Surface: A Molecular Dynamic Study - Kaphle, Gopi Chandra; Khadka, Prabin; Bhatta, Khemraj; Bhujel, Pradeep; Bhatta, B.; Paudel, Dasu Ram; KC, Mukunda; Acharya, Druba Prasad (Pragya Darshan प्रज्ञा दर्शन, 2025)
Computational simulation techniques have become increasingly powerful and widespread due to advancements in computing capabilities which provide valu- able insights into the behavior, properties, and interactions of nanoscale systems to accelerate development, optimize designs, and improve the safety and efficacy of nanomaterial-based applications. In the current study, adsorption equilibrium coefficients and free energy of some aromatic acids are calculated at different temperatures using molecular dynamics simulation along with free enegrgy calcu- lation to investigate the adsorption behavior of aromatic acid on graphene surface with temperature. The effect of temperature on the adsorption behavior of cer- tain aromatic acids -salicylic acid, benzoic acid, and phthalic acid- on carbon nanotubes was investigated using molecular dynamics simulation and free energy calculations at three different temperatures 260K, 300K, and 340K. Current anal- yses show that, in all temperature, salicylic acid has the highest adsorption and phthalic acid has the lowest (phthalic acid < benzoic acid < salicylic acid). It is discovered that the amount of carboxylic acids that adsorb on carbon nanotubes increases with temperature. Keywords: carbon nanotube, aromatic compounds, free energy calculation, adsorption equilibrium constant